1990
DOI: 10.1002/aic.690361014
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of cumene in H‐ZSM‐8 and modified H‐ZSM‐8 Zeolites

Abstract: ZSM-8 zeolite is a medium-pore (pore size = 0.6 nm) high-silica zeolite, belonging to a pentad family of zeolites, introduced by Mobil Oil Corporation in 1971. The X-ray diffraction spectrum of ZSM-8 is somewhat similar to that of ZSM-5, which is a very widely investigated zeolite, except for a splitting in the highest peak in the region 28 = 22-25O observed for ZSM-8 (Lechert, 1984). Earlier studies (Akolekar and Choudhary, 1987) have indicated that the influence of degree of Hi -exchange and calcination temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, sorption/diffusion in the zeolite from the liquid phase is relatively less investigated. Liquid-phase singlecomponent sorption/diffusion of o-and m-xylenes and mesitylene (Choudhary and Singh, 1986), C 1 -C 4 alcohols (Lin and Ma, 1988), cumene Choudhary and Mamman, 1990), and C 2 -C 8 alcohols, n-hexane, and n-butylamine (Choudhary et al, 1992) in ZSM-5 zeolite has been reported earlier. The diffusion in ZSM-5 from the liquid phase is expected to differ from the gas-phase diffusion because of the lower degree of freedom for the orientation of liquid sorbate molecules and also due to the requirement of additional energy (equivalent to enthalpy of vaporization) for pulling out the sorbate molecules from their bulk liquid during their entrance in the zeolite channels.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, sorption/diffusion in the zeolite from the liquid phase is relatively less investigated. Liquid-phase singlecomponent sorption/diffusion of o-and m-xylenes and mesitylene (Choudhary and Singh, 1986), C 1 -C 4 alcohols (Lin and Ma, 1988), cumene Choudhary and Mamman, 1990), and C 2 -C 8 alcohols, n-hexane, and n-butylamine (Choudhary et al, 1992) in ZSM-5 zeolite has been reported earlier. The diffusion in ZSM-5 from the liquid phase is expected to differ from the gas-phase diffusion because of the lower degree of freedom for the orientation of liquid sorbate molecules and also due to the requirement of additional energy (equivalent to enthalpy of vaporization) for pulling out the sorbate molecules from their bulk liquid during their entrance in the zeolite channels.…”
Section: Introductionmentioning
confidence: 78%
“…Apart from the sorbate factors, the diffusion in ZSM-5 zeolite has been found to be strongly influenced by a number of zeolite factors, such as Si/Al ratio, degree of cation exchange, thermal/hydrothermal treatments, presence of strongly sorbed species or foreign materials, etc. (Post et al, 1984;Wu and Ma, 1984;Choudhary and Srinivasan, 1986b;Choudhary and Mamman, 1990). Hence, the diffusivi- ties in different ZSM-5 type zeolites can seldom be compared.…”
Section: Resultsmentioning
confidence: 99%
“…[143] The incorporation of phosphorus has been carried out by several methods like wet impregnation with H3PO4 [144] and NH4H2PO4, [138] or by gas deposition of PCl3 [145] P(OCH3)3 [146] or P(CH3)3, [136] among others. The most studied materials include zeolites ZSM-5, [136,147,148] USY, [149,150] Beta, [151] ZSM-8, [152] MCM-22, [153] and mesoporous MCM-41 zeolite. [154] Despite the large number of studies on phosphorus incorporation, the phosphorus-zeolite interaction is still unclear, and several interaction theories have been proposed to explain the observed properties of the final catalysts.…”
Section: Phosphorus Incorporation In Zeolitesmentioning
confidence: 99%